Management of Information and Documentation Centers: A Content Analysis on the Literature in Turkey - Kurulgan, Mesut; İspir, Burçin (Information World, 2009)
The main aim of this study is to analyze reflections of the information and documentation center studies on the library literature in Turkey. Based on this aim, the articles which had been published in “Türk Kütüphaneciliği” and “Bilgi Dünyası” journals between the years of 2000-2008, was analyzed with content analysis method. The main finding of this study is the easily observable increase of information management center studies in the analyzed years. The most examined subject related to the information and documentation center is planning, the least examined subject related to information and documentation center is controlling. The articles which were analyzed were mostly the theoretical articles.
Keywords: Information centres; Libraries; Management; Organization; Content analysis; Librarianship; Journals